Fluorescent Polystyrene Films for the Detection of Volatile Organic Compounds Using the Twisted Intramolecular Charge Transfer Mechanism † - Borelli, Mirko (Molecules, 2017)
Thin films of styrene copolymers containing fluorescent molecular rotors were demonstrated to be strongly sensitive to volatile organic compounds (VOCs). Styrene copolymers of 2-[4-vinyl(1,1′-biphenyl)-4′-yl]-cyanovinyljulolidine (JCBF) were prepared with different P(STY-co-JCBF)(m) compositions (m% = 0.10–1.00) and molecular weights of about 12,000 g/mol. Methanol solutions of JCBF were not emissive due to the formation of the typical twisted intramolecular charge transfer (TICT) state at low viscosity regime, which formation was effectively hampered by adding progressive amounts of glycerol. The sensing performances of the spin-coated copolymer films (thickness of about 4 µm) demonstrated significant vapochromism when exposed to VOCs characterized by high vapour pressure and favourable interaction with the polymer matrix such as tetrahydrofurane (THF), CHCl(3) and CH(2)Cl(2). The vapochromic response was also reversible and reproducible after successive exposure cycles, whereas the fluorescence variation scaled linearly with VOC concentration, thus suggesting future applications as VOC optical sensors.